Room-Temperature Solid-State Maser Amplifier - Tom Day; Maya Isarov; William J. Pappas; Brett C. Johnson; Hiroshi Abe; Takeshi Ohshima; Dane R. McCamey; Arne Laucht; Jarryd J. Pla (Physical Review X)
Masers once represented the state of the art in low-noise microwave amplification technology but eventually became obsolete due to their need for cryogenic cooling. Masers based on solid-state spin systems perform most effectively as amplifiers, since they provide a large density of spins and can, therefore, operate at relatively high powers. While solid-state maser oscillators have been demonstrated at room temperature, continuous-wave amplification in these systems has only ever been realized at cryogenic temperatures. Here, we report on a continuous-wave solid-state maser amplifier operating at room temperature. We achieve this feat using a practical setup that includes an ensemble of nitrogen-vacancy center spins in a diamond crystal, a strong permanent magnet, and a simple laser diode. We describe important amplifier characteristics including gain, bandwidth, compression power, and noise temperature and discuss the prospects of realizing a room-temperature near-quantum-noise-limited amplifier with this system. Finally, we show that in a different mode of operation the spins can be used to reduce the microwave noise in an external circuit to cryogenic levels, all without the requirement for physical cooling.